2020
DOI: 10.7759/cureus.10636
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Hypothyroidism (SH) and Atherogenic Index of Plasma (AIP) in Women: A Case-Control Study From a Tertiary Care Hospital in South India

Abstract: Introduction Subclinical hypothyroidism (SH) is defined as an increase in serum-thyroid stimulating hormone (S-TSH) above the normal level with free triiodothyronine (T4) and free thyroxine (T3) within the normal range. It is more common in females. The association between SH and dyslipidemia is unclear. There are many controversial studies regarding the same. This is the single largest study of Atherogenic index of plasma (AIP) in SH among women from our country. Our aim is to study the lipid profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…The elevated AIP among subclinical hypothyroidism is due to increased TG and decreased HDL-C compared to normal euthyroid control. The mean AIP of subclinical hypothyroid females revealed that SCH females were at higher risk for cardiovascular disease than euthyroid females [25].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The elevated AIP among subclinical hypothyroidism is due to increased TG and decreased HDL-C compared to normal euthyroid control. The mean AIP of subclinical hypothyroid females revealed that SCH females were at higher risk for cardiovascular disease than euthyroid females [25].…”
Section: Discussionmentioning
confidence: 97%
“…The decrease in fT3 and fT4 is characterized by primary hypothyroidism with increased serum TSH due to a feedback mechanism by the hypothalamus-pituitary-thyroid axis [25]. The diagnosis of subclinical hypothyroidism is based on laboratory variables as the patient does not show symptoms, unlike with primary hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation